Approach to the Functional Importance of Acropora cervicornis in Outplanting Sites in the Dominican Republic - Calle-Triviño, Johanna; Muñiz-Castillo, Aarón Israel; Cortés-Useche, Camilo; Morikawa, Megan; Sellares-Blasco, Rita; Arias-González, Jesús Ernesto (Frontiers in Marine Science, 2021)
Coral restoration has been recognized as an increasingly important tool for coral conservation in recent years. In the Caribbean, the endangered staghorn coral, Acropora cervicornis has been studied for restoration for over two decades with most studies focusing on evaluating simple metrics of success such as colony growth and survivorship in both nurseries and outplanted sites. However, for reef restoration to aid in the recovery of ecological function in outplanted sites, there is a need to measure the functional ecology of the impact of outplanting. Here, we present and identify positive ecological processes and ecological functions (such as increased fish biomass, coral cover, and increased in structural complexity) relative to active reef restoration. In the Southeastern Reefs Marine Sanctuary in the Dominican Republic, we monitored the percentage of benthic cover and fish biomass alongside active reef restoration over the period of 12 months in four zones. Subsequently, we developed multidimensional analyses in conjunction with generalized linear models (GLM) and linear models. Our results show there is a remarkable spatial and temporal differentiation favoring greater ecological function in restored areas. We observed the most noticeable patterns of change in the benthos and coral species composition. We found a positive relationship between amounts of outplanted colonies with the total fish biomass for the three outplanted sites. We highlight that Scarus iseri, a parrotfish critical for grazing maintenance, was the species with the greatest benefit. Our results provide evidence of the functional importance of Acropora cervicornis in coral reef active restoration efforts.